PENGARUH STRATEGI KWL (KNOW,WANT TO KNOW,LEARNED) TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 128 HARAPAN KECAMATAN MAPPEDECENG KABUPATEN LUWU UTARA - Cahaya, Putri; Sukri Syamsuri , Andi; Saeful, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT Putri Cahaya. 2026. The Effect of KWL (Know, Want to Know, Learned) Strategy on Reading Comprehension Skills of Fifth Grade Students at SD Negeri 128 Harapan, Mappadeceng District, North Luwu Regency.Thesis. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Makassar. Supervised by Andi Sukri Syamsuri and Muhammad Saeful.Thisstudy aims to analyze the effect of the KWL (Know, Want to Know, Learned) strategy on students’ reading comprehension skills. The research problem of this study is: “How does the KWL (Know, Want to Know, Learned) strategy affect the reading comprehension skills of fifth grade students at SD Negeri 128 Harapan, Mappadeceng District, North LuwuRegency?” This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest design. The population consisted of all fifth grade students at SD Negeri 128 Harapan, with a total sample of 23 students selected through total sampling technique. Data were collected through learning outcome tests conducted before the treatment (pretest) and after the treatment (posttest). The data were analyzed using descriptive statistics and inferential statistics, including normality tests and paired sample t-test with the assistance of SPSS software. The results showed an increase in the students’ average scores from 41.96 in the pretest to 77.83 in the posttest. The hypothesis testing results indicated a significance value of 0.000 < 0.05, meaning that there was a significant difference between the pretest and posttest results. In addition, the observation results showed that students’ learning activities were categorized as good.In conclusion, the use of the KWL (Know, Want to Know, Learned) strategy has a significant and effective effect on the reading comprehension skills of fifth grade students at SD Negeri 128 Harapan.